Power through standards: The Federal Conference for Outcome Measurement and Benefit Assessment of Chronic Wounds - Augustin, M.; Mayer, A.; Heyer, K.; Storck, M.; Debus, E. S. (Phlebologie, 2016)
Background When concerning documentation and follow up measurement for chronic wounds, uniform standards are a vital precondition for further development of care in Germany. The Federal Consensus Conference “Outcome Measurement and Benefit Assessment for Chronic Wounds” has taken action and has approved systematic recommendations including small data records since 2013.Aim In the following review rationales, objectives, methods and action outcomes of the Federal Consensus Conference are summarized.Results Experts from more than 25 different scientific expert associations, professional associations, organizations specialized in care, representatives of statutory health insurance companies as well as the Federal Ministry of Health participated in the consensus formation. From 2013–2015 a total of eight consensus meetings as well as six online consensus enquiries were agreed upon. These entailed a) the relevant subject areas for consensus formation, b) the necessary standards for wound documentation, c) recommendations concerning the enquiries on quality of life for people with chronic wounds, d) recommendations for minimal clinically relevant differences, e) standards on utilization of secondary data and f) recommendations for health-economic analytics of ulcus cruris. The first four publications concerning this topic were finalized.Conclusions The combination of personal attendance meetings and online enquiries with a broad panel of experts has proved to be an efficient tool for consensus formation regarding the documentation criteria and outcome criteria for chronic wounds using the example of ulcus cruris. The present results are subject of an active implementation in 2016/2017 and at the same time provide a chance for an improved process- and result quality concerning nationwide care.Hintergrund Einheitliche Standards in der Dokumentation und Verlaufsmessung chronischer Wunden sind eine unerlässliche Voraussetzung für die Weiterentwicklung der Versorgung in Deutschland. Die Bundeskonsensus-konferenz “Ergebnismessung und Nutzenbe-wertung in der Versorgung chronischer Wunden” hat darauf reagiert und seit 2013 systematische Empfehlungen inklusive minimaler Datensätze konsentiert.Zielsetzung In der vorliegenden Übersichts-arbeit werden Rationale, Zielsetzungen, Methoden und Handlungsergebnisse der Bundeskonsensuskonferenz zusammengefasst.Ergebnisse An der Konsensusbildung beteiligt waren Experten von über 25 wissenschaftlichen Fachgesellschaften, Berufsver-bänden, Pflegeorganisationen, Vertretern der gesetzlichen Krankenkassen sowie des Bundesministeriums für Gesundheit. In insgesamt acht Konsensussitzungen sowie sechs Online-Konsensusabfragen wurden in den Jahren 2013–2015 a) die relevanten Themenbereiche zur Konsensusbildung, b) die not-wendigen Standards für die Wunddokumentation, c) Empfehlungen für die Erhebung von Lebensqualität bei chronischen Wunden, d) Empfehlungen zu minimalen klinisch relevanten Differenzen, e) Standards für die Nutzung von Sekundärdaten und f) Empfehlungen zur gesundheitsökonomischen Analytik beim Ulcus cruris konsentiert. Die ersten vier Publikationen zum Thema wurden finalisiert.Schlussfolgerung Die Kombination aus Präsenzsitzungen und Onlineabfragen mit einem interdisziplinären Expertenpanel hat sich als effizient zur Konsensusbildung der Dokumentations- und Outcome-Kriterien bei chronischen Wunden am Beispiel des Ulcus cruris erwiesen. Die vorliegenden Ergebnisse sind Gegenstand einer aktiven Implementierung in den Jahren 2016/2017 und zugleich eine Chance auf eine verbesserte Prozess- und Ergebnisqualität in der bundesweiten Versorgung.
Keywords: Outcome measurement; benefit assessment; chronic wounds; standard guidelines